Factors affecting informal patient payments: a systematic literature review. Issue 2 (22nd May 2019) - Meskarpour Amiri, Mohammad; Bahadori, Mohammadkarim; Motaghed, Zahra; Ravangard, Ramin
Abstract : Purpose: Informal payments (IPs) for healthcare are a serious obstacle to equitable access and universal health coverage in developing countries. Policy makers need to know more about the hidden nature of informal patient payments (IPPs) before any policy adoption and implementation. The purpose of this paper is to systematically review the main factors affecting IPPs. Design/methodology/approach: This systematic review was conducted in 2018 using the standard guideline of PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses. All English original articles on the determinants of IPPs published in the scientific journals, whose full text was available through Scopus, PubMed and Web of Science databases, which were given consideration for review. Findings: The results showed that IPPs were greatly dependent on the characteristics of healthcare consumers, providers, healthcare system and services. Among healthcare consumers' characteristics affecting IPPs, the income, age, education, gender, employment and health status were more cited factors, respectively. Among healthcare providers' characteristics affecting IPPs, the providers' experience, reputation, and salary satisfaction were better known, respectively. Among healthcare services features, the hospitalization, service specialty and the level of treatment urgency were more noted, respectively. Originality/value: Policy making against IPs in the health sector requires precise attention to all components of healthcare market, including healthcare consumers, providers, healthcare system and services characteristics.